ANALISIS PENGARUH CSR TERHADAP CORPORATE REPUTATION DAN BRAND AWARENESS BANK MANDIRI (Studi pada Mahasiswa Undip Semarang) - Ayu, Elva Putri Kusumaning; Kusumawardhani, Amie (Faculty of Economics and Business Diponegoro University, 2015)
The purpose of every business is not only looking for a sustainable profit, but alsoto develop the society, including in universities. This purpose can be achieved by implementing social responsibility. Therefore, the aim of this study is to analyze the effect of corporate social responsibility (CSR) on brand awareness through company reputation of Mandiri Bank.Population of this study is Diponegoro University students who have saving account at Mandiri Bank. As many as 108 respondents were tahen as sample in this study. Structural Equation Modeling (SEM) was applied in this study and AMOS version 21.0 was used to analyze data.The study found that corporate social responsibility has a direct positive and significant effect on brand awareness. Furthermore, the result also showed that CSR affects brand awareness indirectly thourgh corporate reputation.